ESTUDIO DE CARBOHIDRATOS EN VARIEDADES MEXICANAS DE FRIJOL PHASEOLUS VULGARIS L Y PHASEOLUS COCCINEUS L - RODRIGUEZ COQUIEZ, CONSUELO; ORTEGA DELGADO, MARIA LUISA (Centro de Economía Agrícola, Colegio de Posgraduados, 1979)
si
AGRO
Keywords: ESTUDIO, CARBOHIDRATOS, VARIEDADES, FRIJOL, PHASEOLUS VULGARIS L, PHASEOLUS COCCINEUS L; CIENCIAS AGRARIAS; AGRONOMIA; PROTECCION DE LOS CULTIVOS